Rainfall effects to the performance of subsurface flow constructed wetlands in leachate treatment [compact disc] - 339547 Lee, Yun Fook (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Awam - Pengurusan Alam Sekitar)) - Universiti Teknologi Malaysia, 2005